Results of the Diaphragmatic Plication Database: 10 Years' Experience - Kosse, Nils Jurriaan; Galetin, Thomas; Schwarz, Sarah Bettina; Mathes, Tim; Koryllos, Aris; Lopez-Pastorini, Alberto; Beckers, Frank; Stoelben, Erich (The Thoracic and Cardiovascular Surgeon, 2021)
Background Unilateral diaphragmatic paralysis or paresis (UDP) in adults is an often overlooked disease which relevantly impairs the patient's lung function and quality of life. Particularly in idiopathic UDP, there is no evidence for conservative therapy and only little evidence for surgical therapy.Methods The method involves retrospective single-center analysis of patients with UDP persistent for at least 1 year who were operated by diaphragmatic resection, plication, and augmentation with a polypropylene mesh. The patients were tested for lung and diaphragmatic function, six-minute walk test (6MWT), and blood gas analysis before, 3 and 12 months after surgery.Results In total, 85 patients received surgery for UDP. The most frequent reasons for UDP were idiopathic (67%), iatrogenic (mainly cardiac and cervical spine surgery; 24%), and trauma (9%). The mean operation time was 84 ± 24 minutes, the length of hospital stay 8.4 ± 3.9 days, chest tubes were removed after 11.7 ± 4.1 days. Overall morbidity was 42%, mortality 0%. Forced expiratory volume in one second (FEV1) in supine position improved by 12.4% absolute, vital capacity by 11.8% absolute, and sniff nasal inspiratory pressure by 1.4 kPa 12 months after surgery (p <0.001 each). Total lung capacity increased by 6.8% absolute at 12 months (p = 0.001) The 6MWT distance improved by 45.9 m at 3 months and 50.9 m at 12 months (p = 0.001, each).Conclusion Surgical therapy for UDP is highly effective in the long term. The superiority over conservative treatments needs to be evaluated prospectively with standardized physiotherapeutic protocols. FEV1 in supine position and 6MWT are easy to perform tests and represent statistically and patient-relevant outcomes.
Keywords: diaphragm; surgery; disease; quality of life; ventilation